STATE REGULATION OF MIGRATION PROCESSES IN THE KYRGYZ REPUBLIC IN MODERN CONDITIONS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article analyzes the state migration process of the Kyrgyz Republic. An analysis of external labor migration was carried out, issues of development of the system of organized employment in modern conditions were revealed. The positive aspects of labor migration from Kyrgyzstan to the Russian Federation have been identified
Keywords: state migration process, migrants, immigrants, foreign labor, labor migration, migration process.